1997
DOI: 10.2307/3345465
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Texture and Number of Parts on the Ability of Music Majors to Detect Performance Errors

Abstract: The purpose of this study was to examine graduate and undergraduate music majors' ability to detect pitch arid rhythm errors in one-, two-, and three-part settings of texturally contrasting musical excerpts. A stimulus audiotape consisting of 12 excerpts resulted from the following arrangement by texture and number of parts: 4 one-part excerpts, 2 two-part and 2 three-part homorhythmic excerpts, and 2 two-part and 2 three-part polyrhythmic excerpts. Subjects ( N = 150) listened to purposefully marred recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
1
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 17 publications
9
54
1
1
Order By: Relevance
“…It is likely that this was the result of the added difficulty of diagnosing errors in a polyrhythmic setting, a result similar to that found by Byo (1997). However, participants more accurately detected pitch errors in the full ensemble texture as compared with the single section texture.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It is likely that this was the result of the added difficulty of diagnosing errors in a polyrhythmic setting, a result similar to that found by Byo (1997). However, participants more accurately detected pitch errors in the full ensemble texture as compared with the single section texture.…”
Section: Discussionsupporting
confidence: 76%
“…Further study using a larger participant pool and greater control for preparation method seems warranted. Authors of previous research have suggested that rhythm errors were identified correctly more often than pitch errors and that participants' abilities to detect errors were greater when textures were simpler, as opposed to more complex (Byo, 1993(Byo, , 1997Crowe, 1996;Mount, 1982;Sheldon, 1998). The results of the current research indicated that there was a significant interaction between error types (rhythm/pitch) and ensemble textures (full ensemble/single section).…”
Section: Discussionsupporting
confidence: 47%
“…Certain methods in this study closely followed those established by Byo (1997); therefore, musical examples identified for this research were selected according to several criteria. To maximize the potential for discrimination in an error-detection task during an event that marginally approximated a band rehearsal episode, examples contained up to three concurrent yet distinct voice parts.…”
Section: Assessing Error-detection Abilitiesmentioning
confidence: 99%
“…Some have suggested that although it uses certain abilities that may have been cultivated through discrete and tangential activities (e.g., ear training, music theory, private instrumental instruction, ensemble participation), error detection may be a skill into which other peripheral competencies may not be easily transferred or synthesized (Brand & Bursed, 1981;Byo, 1993Byo, , 1997DeCarbo, 1982;Doane, 1989;Forsythe & Woods, 1983;Gonzo, 1971;Larson, 1977;Ramsey, 1979). Brand and Bursed (1981) argue that error-detection abilities must be addressed separately from ear training and theory venues and treated as a unique skill that should be taught with the specific goal of discriminate hearing.…”
mentioning
confidence: 99%
“…Other research investigating amount of training and patterns of listening has found that listeners with more musical training seem to perceive music differently than listeners with less training (Byo, 1997;Flowers, 1985Flowers, , 2000Johnson, 1996;Johnson & Kelly, 1995;Sheldon & Gregory, 1997;Williams, 2005). Listeners with more musical training have been found to perceive tempo decreases with greater accuracy than increases (Sheldon & Gregory, 1997).…”
mentioning
confidence: 99%